DESCRIPTION OF CHARACTERISTICS AND TYPES OF LIVESTOCK FARMING OF SURKHAN OASIS IN B.H. KARMISHEVA RESEARCH - Turaev, Sherzod (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
In the article, the situation of animal husbandry, which is considered the leading farm in the Surkhan oasis, is analyzed on the basis of the researches of scientist B.Kh. Karmisheva. It has been revealed that the types of livestock farming in the late 19th and early 20th centuries were widespread among ethnic groups. Also, opinions were given about the unique role of the scientist in the life of the cattle-breeding oasis.